Experimental results on mechanical behaviour of metal anchors in historic stone masonry - Muñoz, Rosana (2018)
Ancient buildings constructed in stone masonry often deteriorate and partially collapse, with only their façades and/or lateral walls remaining. This work provides a study of the mechanical behaviour of anchors used as connections between existing walls and new members, for purpose of strengthening of historic stone masonry buildings. The paper addresses a comparative analysis between an experimental campaign and analytical formulations for ultimate load prediction. To obtain practical results, pull-out tests were carried out with adhesive and mechanical metallic anchors in stone masonry walls constructed in laboratory. The results allow conclusions on the most efficient connections in terms of adhesion.